Analysis of UAV multicopter of air photography in New Yogyakarta International Airports - Indreswari Suroso; Erwhin Irmawan (Universitas Ahmad Dahlan, 2019)
The higher the quality of the drone, the longer the drone will fly and the better the quality of the drone's photography. Survey of research location in Glagah Indah Beach, preparation of drone at ground, we plan the height of flying drones, then testing drone at ground, we measure camera calibration, and then result capture in the air and images in the air. Vehicle specifications are as follows: Frame: F450; Flight Controller: DJI Naza M-Lite; Propeller: 1045 Prop; motorbike: brushless sunnsky 980 kVa; ESC: Skywalker 40 Ampere 3s; Battery: Ace 3s Gens 5000mAH; Remote: Turnigy 9XR with Frsky Tanseiver; and camera: Xiaomi Yi 4k International edition.This drone type multicopter can penetrate the high of 100 meters to 200 meters and can air for 30 minutes, can take an area of up to 1 km while payload drones multicopter is 2.8 kg.This multicopter drone has a 12 megapixel sensor; maximum flight time of 15 minutes; speed of 20 m/s, maximum take-up speed of 6 m/s, maximum landing speed of 4m/s, temperature range when operating drone 0o to 40oC and maximum image size of 4000x3000.